A low profile miniature RFID tag antenna dedicated to IoT applications. Issue 6 (18th August 2019) - Aslam, Bilal; Kashif, Muhammad; Awais Azam, Muhammad; Amin, Yasar; Loo, Jonathan; Tenhunen, Hannu
ABSTRACT: RFID tag antennas with stable performance on the diverse electromagnetic mounting platforms are an integral part of the ubiquitous RFID systems. This research article presents a novel tag antenna design that facilitates the said objective. The proposed antenna consists of a modified H-shaped slot structure that ensures considerable robustness from the application environment through confining the surface current density within the antenna structure. The antenna offers a tunable bandwidth of 40 MHz within the microwave band of (2.4–2.5) GHz. The proposed tag antenna exhibits excellent response on metallic platforms of different sizes and thicknesses with an effective gain of almost four times of that in free space. Furthermore, the designed tag antenna performs adequately well on low–medium permittivity dielectrics (glass, paper, and plastic) and RF absorbers (water). The free space and on-metal performance of the proposed tag antenna are verified by testing a prototype realized on the FR4 substrate.